Al and Mg Co-Doping Towards Development of Air-Stable and Li-Ion Conducting Li-La-Zirconate Based Solid Electrolyte Exhibiting Low Electrode/Electrolyte Interfacial Resistance. Issue 12 (17th August 2020) - Kobi, Sushobhan; Amardeep; Vyas, Akhilesh; Bhargava, Parag; Mukhopadhyay, Amartya
Abstract : Air-stable solid electrolytes, possessing good Li-ion conductivity and facilitating low resistance at electrode/electrolyte interface, are essential towards facile development/handling of safe-cum-stable solid-state Li-ion batteries, possessing desired power densities. In this context, we report here the design and development of Al/Mg co-doped Li-La-zirconate (LLZO) based solid electrolytes that address the concerns associated with inferior air stability of Al-doped LLZO, while retaining Li-ion conductivity (∼4.7 × 10 −4 s cm −1 ) as good as that for similarly developed Al-doped LLZO and higher than that for Mg-doped counterpart. Doping as "little" as 0.1 mole of Mg-ion (per mole of LLZO), as for the optimized Al(0.2)/Mg(0.1) co-doped LLZO, is sufficient to impart long term phase and structural stability in air, unlike that for Al-doped LLZO. Accordingly, Li-ion conductivity of Al(0.2)/Mg(0.1) co-doped LLZO gets nearly retained even after air-exposure for 50 days, in contrast to lowering of conductivity for Al-doped LLZO by ∼3 orders of magnitude after 24 days. The influence of excellent air stability and Li-ion conductivity could be seen on the Li/LLZO interfacial resistance, with the Al(0.2)/Mg(0.1) co-doped LLZO possessing the lowest area specific resistance of ∼18 Ω cm 2 among those investigated, which is also among the lowest reported to-date, without any additional surface/interfacial engineering being done.